Perbandingan Kritik Sastra Masa Umayyah dan Abbasiyyah - Nadia Rahmi (Alfaz (Arabic Literatures for Academic Zealots), 2021)
The purpose of this article is to see how the development of literary criticism during the Umayyad and Abbasid times, and to increase knowledge more broadly about Arabic literary criticism. As for the results of this study, namely literary criticism during the Umayyah and Abbasiyyah periods, there are differences and changes. This difference can be seen that during the Umayyad period, literary criticism was focused more on three areas, namely the Hijaz, Iraq and Syria. These three areas have different literary criticism themes. In the Hijaz region, literary criticism contained the Ghazal theme, in Iraq it contained the theme Fakhar and i'tiza, in Iraq there was also criticism of Polemic poetry and literary plagiarism, while in the Syrian region it contained the theme Madh. In contrast to the Abbasid literary criticism which no longer focuses its criticism on the division of regions, but literary criticism developed during the Abbasid era prioritizing literary criticism in terms of rhetoric.